400 must-have words for the TOEFL - Stafford-Yilmaz, Lynn; Zwier, Lawrence J. (New York : McGraw-Hill, 2005)
A study guide and textbook to help you master the core vocabulary and basic written and spoken language skills of the TOEFL
Nature -- Science -- Mind and body -- Society -- Money -- Government and justice -- Relationships -- Culture. 400 must-have words for the TOEFL
Keywords: Test of English as a Foreign Language -- Study guides; English language -- Textbooks for foreign speakers; English language -- Examinations -- Study guides; Vocabulary -- Examinations -- Study guides